2008
DOI: 10.1348/135910707x248959
|View full text |Cite
|
Sign up to set email alerts
|

Does hope predict adjustment to end‐stage renal failure and consequent dialysis?

Abstract: It appears that hope is a significant predictor of adjustment to ESRF. Clinical implications of this research are discussed, along with suggestions for future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
50
2
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 52 publications
3
50
2
4
Order By: Relevance
“…The role of hope in the lives of patients with ESRD is an under-researched topic. My findings therefore add to the very limited claims about its role amongst this group of patients which reports that more hope was positively associated with reduced anxiety, depression, and improved mental health and QOL (Billington et al, 2008) and that keeping hope for a kidney transplant is an important factor in people"s ability to cope with ESRD and HD treatment and links to better QOL (Dencheva, 2010;Moran et al, 2010). However, contrary to my findings, other researchers found that hope has been found to be negatively related to general maladjustment (Cramer and Dyrkacz, 1998) and symptoms of depression (Chang, 2003).…”
Section: Spirituality Religiosity and Quality Of Life And General Wementioning
confidence: 71%
“…The role of hope in the lives of patients with ESRD is an under-researched topic. My findings therefore add to the very limited claims about its role amongst this group of patients which reports that more hope was positively associated with reduced anxiety, depression, and improved mental health and QOL (Billington et al, 2008) and that keeping hope for a kidney transplant is an important factor in people"s ability to cope with ESRD and HD treatment and links to better QOL (Dencheva, 2010;Moran et al, 2010). However, contrary to my findings, other researchers found that hope has been found to be negatively related to general maladjustment (Cramer and Dyrkacz, 1998) and symptoms of depression (Chang, 2003).…”
Section: Spirituality Religiosity and Quality Of Life And General Wementioning
confidence: 71%
“…Consistent with this postulation, Myers and Myers (1999) found that control by physicians explained a substantial portion (35%) of the variance in treatment adherence amongst patients with cystic fibrosis. In addition, some researchers have posited that control by health professionals and control by non-health professionals represent relatively independent dimensions (e.g., Billington, Simpson, Unwin, Bray, & Giles, 2008; McQuillen, Licht, & Licht, 2003), but only a few studies have used separate subscales to assess these two sources of interpersonal control (e.g., Billington et al, 2008; De las Cuevas, Peñate, & Sanz, 2014). Further effort should be made to distinguish the benefits and costs of these sources of interpersonal control after more studies have been conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Previous researchers [6][7][8][9] suggested that hope predicts psychological adjustment and the self-worth of ill individuals. Consistent with the extant literature, we found that hope also predicted rehabilitation behavior, subjective well-being, and rehabilitation beliefs in the context of sport injuries.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Researchers in the field of medicine and health psychology consider hope an important factor in helping people to persevere when they face challenges and threats, such as end-stage renal failure, chronic pain, traumatic physical disability, and sport injury. [6][7][8][9] Important features of the hope model 4,5 are the 2 components that shape one's hope perception: the ability to initiate and to maintain the actions necessary to reach a goal (ie, hope agency) and the positive belief that one is able to generate routes to goals (ie, hope pathways). In sport settings, empirical evidence 10,11 showed that both agentic thinking and pathways to formulate one's hope perception are very important.…”
mentioning
confidence: 99%